Language as a way of shaping our identity, idea and action - Neupane, Rebati Prasad (Bodhi: An Interdisciplinary Journal, 1970)
DOI: http://dx.doi.org/10.3126/bodhi.v4i1.5819 Bodhi 2010 4(1): 191-197
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEyNi9ib2RoaS52NGkxLjU4MTk